ANALISIS PENERAPAN PSAK 101 TENTANG PENYAJIAN LAPORAN KEUANGAN SYARIAH TERHADAP KUALITAS LAPORAN KEUANGAN SYARIAH PADA PT BANK SYARIAH INDONESIA (SURADE) DAN BAZNAS KABUPATEN SUKABUMI - Mutiara, Tia; Kartini, Tina; Nugroho, Gatot Wahyu (COMPETITIVE, 2023)
This study aims to determine how the implementation of PSAK 101: presentation of Islamic financial statements on Islamic entities that have been mentioned in PSAK 101 which includes Bank, Insurance, Waqf and Amil entities. This research was conducted on Bank and Amil entities, case studi on BAZNAS Sukabumi Regency and Bank Syariah Indonesia Tbk (Surade).  The method used in this study is a qualitative descriptive method. Where the researcher is the key instrument, and the data collection technique is done by triangulation (combined) data is inductive/qualitative. From the results of the studi, it was concluded that PT Bank Syariah Indonesia Tbk (Surade) was not in accordance with PSAK 101, there were several formats and account names that were not appropriate. And does not explain cash flow reports, reports on changes in equity, reports on receipts and distribution of zakat funds, report on receipts and uses of benevolent  funds, and CALK. Meanwhile, BAZNAS Sukabumi Regency is in line with PSAK 101. However,there are several formats and account names that do not match. Also, there is not report on changes in assets under management.